Learning styles and its significance in health personnel education - Nurumal, Mohd. Said (IIUM Press, International Islamic University Malaysia, 2018)
This research book named “Learning styles and its significance in Health Care Personnel Education” is intended to provide a clear, concise and user-friendly approach for readers and young researchers regarding the vital issues in teaching and learning especially in learning styles and its significance among health care personnel.We understand that learning style is defined as how individuals prefer to learn or their steady way of responding and using stimuli in the aims of improving their learning. Learning styles have been an aid to reflection as it helps health care personnel to reflect appropriately on patient care. Without understanding the learning styles, it can be quite challenging to reflect on a situation as reflection stages involve thinking and learning in order to produce a better outcome.This book has four chapters such as students’ learning style among health related programs students, impact of self-efficacy in teaching and learning, interpersonal communication skills in teaching and learning and impact of advanced technology (smart phones) in learning.This research book explores some evidence findings in health care personnel education. evidence-based approach to teaching and learning is crucial to maximising student outcomes. We need to know there is needed to have evidence about the performance of our students in order to support them to achieve high quality educational outcomes.